Mentari's guide validation as a guidelines in teaching bath skills for tunagrahita children - Tiara Rizky Utami; Budi Andayani (Universitas Pendidikan Ganesha, 2020)
Bathing skill was an important skill that should be possessed by intellectual disability children so that they become independent. The result of preliminary study indicates that mothers of the intellectual disability did not have knowledge and skills in teaching children’s bathing skill so they often help their children to take a bath. Based on the matter, it requires a guide to improve mothers’ knowledge and skill in teaching bath skill for intellectual disability children. This research is aimed to perform the validation of MENTARI guide through content validation with professional judgment and empirical validation which uses one-group pretest-posttest. Wilcoxon’s Signed Rank Test was utilized to test the score difference between knowledge and skill of teaching intellectual disability children to take a bath themselves. Nine mothers who have intellectual disability children become the participants. The research result indicates that MENTARI guide was contently and empirically valid. The guide has also satisfying content validity (Aiken’s V= 0,80-0.98). The data analysis which utilizes Wilcoxon’s Signed Rank Test indicates that there was an increase of score of bathing teaching knowledge and skill with Z =-2,670 and p<0.05 for knowledge score and Z value = 2,670 and p< 0.05 for bathing teaching skill score.